2019
DOI: 10.1002/ccd.28320
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural P2Y12 inhibition and decrease in platelet count following transcatheter aortic valve replacement

Abstract: Background Thrombocytopenia after transcatheter aortic valve replacement (TAVR) is associated with adverse clinical outcomes. Whether preprocedural P2Y12 inhibition prevents postprocedural thrombocytopenia is uncertain. Methods This retrospective analysis identified consecutive patients (n = 266) undergoing TAVR between November 2016 and July 2017. Preprocedure clopidogrel load ≥300 mg or maintenance P2Y12 inhibitor therapy defined preprocedural P2Y12 inhibition. Patients who did not consent for the registry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…32,33 Ibrahim et al found that patients receiving a clopidogrel loading dose before TAVR showed a significantly lower DPC. 20 This finding supports the hypothesis of an increased platelet consumption through activation, since clopidogrel inhibits platelet aggregation.…”
Section: Impact Of Pharmacological Agents On Platelet Count After Tavrsupporting
confidence: 84%
See 1 more Smart Citation
“…32,33 Ibrahim et al found that patients receiving a clopidogrel loading dose before TAVR showed a significantly lower DPC. 20 This finding supports the hypothesis of an increased platelet consumption through activation, since clopidogrel inhibits platelet aggregation.…”
Section: Impact Of Pharmacological Agents On Platelet Count After Tavrsupporting
confidence: 84%
“…The percentual change 6 h after TAVR was calculated for platelet count (DPC = 100 × [baseline platelet count – 6 h platelet count]/baseline platelet count) and vWF:Ac/Ag ratio (ΔvWF = 100 × [baseline vWF:Ac/Ag ratio – 6 h vWF:Ac/Ag ratio]/baseline vWF:Ac/Ag ratio). In previous publications, different cut‐off values at 50% (at nadir), 10 30% (at nadir), 13 or 20% (after 1 day) 20 were used. To analyze possible causative factors in the present study early DPC was analyzed, accordingly a lower DPC at 20% was chosen as cut off value.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, even nuisance thrombocytopenia may cost substantial resources by increasing hospital stay [10]. Several general mechanisms to explain post-TAVI thrombocytopenia have been proposed, including drug toxicity (e.g., heparin, aspirin, clopidogrel, warfarin, and novel oral anticoagulants), thromboinflammation, increased platelet consumption, mechanical damage due to shear stress (e.g., in case of paravalvular leak), activation of the coagulation cascade, decreased platelet production, and impaired platelet renewal, as well as dilution pseudothrombocytopenia [4,[11][12][13][14][15]. Further understanding the causes of thrombocytopenia is urgently needed to improve next-generation devices.…”
Section: Introductionmentioning
confidence: 99%
“…3 New data suggest that P2Y 12 inhibition prior to the procedure may blunt the severity of TAVR-associated thrombocytopenia. 8 In-hospital and early thromboembolic event rates after TAVR range between 2-4%. 9 More than 70% of these events occur within 2 days of the procedure.…”
mentioning
confidence: 99%